2016
DOI: 10.3892/ol.2016.5259
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes during lung carcinogenesis-modulation by curcumin and quercetin

Abstract: The aim of the present study was to examine the effectiveness of curcumin and quercetin in modulating ultrastructural changes during lung carcinogenesis. A total of 24 male laka mice were divided into the normal control, benzo[a]pyrene (BP)-treated, BP+curcumin-treated, BP+quercetin- treated, and BP+curcumin+quercetin-treated groups (n=6 per group). Lung carcinogenesis was induced by a single intraperitoneal injection of BP [100 mg/kg of body weight (b.wt.)]. Curcumin was supplemented to mice at a dose level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In the present study, LPS also produced obvious ultrastructural damage to lung tissues, whereas curcumin remarkably alleviated lung damage and ameliorated the ultrastructure of lung tissue in LPS‐treated ducks. Consistent with the present results, Wang et al 29 . indicated that combined supplementation with curcumin and quercetin effectively preserved the histoarchitecture as well as ultra‐histoarchitecture in lung carcinogenesis of mice.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, LPS also produced obvious ultrastructural damage to lung tissues, whereas curcumin remarkably alleviated lung damage and ameliorated the ultrastructure of lung tissue in LPS‐treated ducks. Consistent with the present results, Wang et al 29 . indicated that combined supplementation with curcumin and quercetin effectively preserved the histoarchitecture as well as ultra‐histoarchitecture in lung carcinogenesis of mice.…”
Section: Discussionsupporting
confidence: 92%